A COMPARATIVE ANALYSIS OF ENGLISH AND RUSSIAN TRANSLATION OF SPECIALIZED OIL AND GAS TERMINOLOGY (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
This article studies how English oil-and-gas terms are translated into Russian. We ask which strategies translators use most often and why. A small corpus of 150 terms from drilling, production, and HSE documents was analyzed. We coded each item by strategy: borrowing/transliteration, calque, functional equivalent, descriptive translation, and reduction/expansion. Results show a clear preference for functional equivalents and controlled vocabulary when such terms exist, while borrowings appear mainly for global brands or new tools. Calques work for stable technical compounds but not for culture-bound abbreviations. We discuss typical risks (polysemy, false friends, standards) and give practical examples. The study confirms that consistent terminology work and attention to Russian standards improve clarity and safety in technical texts.